(n/4 - 1) slices
The pizza would be divided into n slices, which in turn would be split among 4 people:
= (n/4) slices per person
Harris must have eaten (n/4 - 1) slices.
4 friends evenly dividing up a n - slice pizza
So each one get slices of pizza.
For example, if n = 12 slice then each friend gets 12/4 = 3 pieces. If Harris ate one slice less then he ate =3 -1 = 2 pieces.
So the general expression for slices of pizza did Harris eat is
answer: a. 74
it shows divided evenly, so add the 37+37 = 74
lets say, first number = x
second number = 3x+7
total = 49
4x+7 = 49
4x = 42
x = 42/4
3x+7 = 3(10.5)+7 = 93.8